Navigating Foreign Language Teaching Anxiety: Insights from Pre-Service Teachers during Teacher Professional Education Practicum - Sanjaya, Masud Madhani; Nurkamto, Joko; Sumardi, Sumardi (Indonesian Journal of EFL and Linguistics, 2024)
This study focuses on the experiences of pre-service teachers that may trigger anxiety and delve into the potential benefits and effectiveness of FLTA in enhancing language acquisition and proficiency. By conducting in-depth studies and investigations on this topic, researchers look at the impact of FLTA. They can better understand how FLTA can optimize their problem-solving skills to facilitate language learning and provide valuable insight for language education, especially in EFL classrooms. This study used a narrative strategy to investigate the pre-service EFL teachers' experiences with teaching foreign language anxiety during their teaching practice while enrolled in the Teacher Profession Education Program. The subjects of this study were 3 English pre-service teachers who had completed teaching practice in junior and senior high schools during a professional teaching program in the city of Solo and its surroundings, Central Java, Indonesia. As a result of this study, several sources contributed to participants' experience of teaching foreign language anxiety, such as self-perception of language proficiency, leading inexperience, lack of student interest, fear of negative evaluation, and lack of time and class management. Participants in the teaching practicum also attempt to confront and overcome their worries; the strategies are personal coping strategies, professional coping strategies, social coping strategies, and institutional coping strategies. Although the participants experienced some anxiety while teaching practicum, they overcame it through various strategies. So, leading practicum activities from one meeting to the following allowed participants to develop their abilities and overcome their concerns about teaching in the EFL classroom.